2023
DOI: 10.3390/polym15030613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gamma Radiation on the Processability of New and Recycled PA-6 Polymers

Abstract: The growing quantities of plastic waste have raised environmental concerns, with almost a quarter of disposed plastics being sent to landfill. This has motivated research efforts into various recycling technologies to ease dependence on fossil resources, increasing circularity. Irradiation of various kinds, such as electron beam, beta and gamma rays, has been studied in the past as a way of revamping end-of-life polymer properties. The present work focuses on the effects of gamma radiation on the processabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Studies [ 15 , 16 ] have shown that irradiation can lead to improved mechanical properties, and that the addition of cross-linking agent, e.g., TAIC, enhances this effect. These studies confirm the findings presented in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Studies [ 15 , 16 ] have shown that irradiation can lead to improved mechanical properties, and that the addition of cross-linking agent, e.g., TAIC, enhances this effect. These studies confirm the findings presented in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Gamma irradiation has been employed in many applications, including radiotherapy, sterilization, microbial decontamination, and material modification. When gamma rays make contact with the materials, several events take place, such as structural changes, bond breaking, free radical creation, cross‐linking, and chain scission [39–41] . Although gamma irradiation has been used to prepare or modify a number of materials for various applications, its use in the supercapacitor field is rare, generally centralized to the modification of carbon‐based materials, [42–44] and a few inorganic materials [45–46] .…”
Section: Introductionmentioning
confidence: 99%
“…When gamma rays make contact with the materials, several events take place, such as structural changes, bond breaking, free radical creation, cross-linking, and chain scission. [39][40][41] Although gamma irradiation has been used to prepare or modify a number of materials for various applications, its use in the supercapacitor field is rare, generally centralized to the modification of carbon-based materials, [42][43][44] and a few inorganic materials. [45][46] We recently reported the use of gamma irradiation to incorporate the carbon dots with ethylenediamine (EDA) and the resulting carbon dots composited with ZnO yielded a significant improvement in the specific capacitance and cycling stability of the supercapacitors.…”
Section: Introductionmentioning
confidence: 99%